The Effect of Firm Size, Current Ratio, and Debt to Equity Ratio on Share Price in Food and Beverage Subsector Manufacturing Companies Listed on the Indonesia Stock Exchange - Khairul Anwar (Jurnal Indonesia Sosial Teknologi, 2024)
The purpose of this study is to understand how company size, liquidity, and capital structure can affect stock prices in the food and beverage industry in Indonesia, so as to provide practical guidance for stakeholders in making financial and investment decisions. This research method uses a sample of 18 manufacturing companies in the food and beverage subsector on the IDX in the 2019-2022 period. Sample selection is carried out by purposive sampling technique, which is a technique that considers and determines samples based on certain criteria. The purposive sampling technique was chosen to ensure that the samples taken are relevant and in accordance with the research objectives. The results of this study show that in the number that means that the independent variable is only able to explain the bound variable of 0.299 or 29.9%. *The Stock Price variable can be explained by 29.9% by variables such as company size, debt to equity ratio, current ratio, return on equity while the remaining 70.1% can be influenced by other factors that are not studied.